Alkylamine Incorporation in Amidoxime Functionalized Polymers of Intrinsic Microporosity for Gas Capture and Separation. Issue 10 (7th September 2020) - Miles, Ashley; Wilfong, Walter C.; Hopkinson, David; Sekizkardes, Ali K.
Abstract : Amidoxime functionalized polymers of intrinsic microporosity (PIMs) are synthesized from postsynthetic functionalization of PIM‐1 with hydroxylamine and processed into chemisorbents with alkylamine incorporation. Strong interaction between functionalized PIM‐1 and primary amines is characterized in detail by diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) study. As‐prepared sorbents not only show the highest CO2 uptake capacity (37.9 cm 3  g −1 at 0.15 bar and 298 K) recorded in reported PIMs, but they also demonstrate tunable, processable, and stable polymeric sorbent design, which can be nanoengineered for other gas capture and separation applications. Abstract : A novel adsorbent design based on polymers of intrinsic microporosity (PIM‐1) is introduced for gas capture and separation applications: the design of the sorbent concisely addresses a strong interaction potential between amines and amidoxime groups. The amine incorporation in the polymeric and processable PIM sorbents results in more than four times CO2 uptake enhancement, compared with neat PIM‐1.